Study on hot air heating characteristics of greenhouse in cold region - Zhang, Chenghu; Zou, Dezhi; Huang, Xinpeng; Wu, Yaling (Frontiers in Energy Research, 2023)
In view of the cold climate characteristics in northeast China in winter, traditional passive energy saving methods are hard to meet the winter load demand of greenhouses, but we can increase the use of all-air heat transfer system, and through the form of air heat transfer to obtain heat. And it is easy to have uneven airflow in the field, resulting in temperature imbalance and affecting the growth and development of crops in the greenhouses, especially to some large wide and low greenhouses. Therefore, the simulation study of the airflow and temperature field in the greenhouses is the main research direction of this paper. In order to solve the problem that the temperature gradient of greenhouse is too large under the conventional heating method, we propose the heating method of full hot air, according to the space size characteristics of greenhouse. Based on the dynamic load characteristics of the greenhouse under the action of heat insulation foundation and double layer film, the hot air heating system of the greenhouse was designed. In order to study the characteristics of the air flow field, temperature field and humidity field of the greenhouse in the form of hot air heating, the numerical simulation modeling and mesh division of the greenhouse in the form of hot air heating were carried out which based on the simulation software of AIRPAK. Based on AIRPAK simulation, this study investigated the characteristics of air flow field, temperature field and humidity field in the greenhouse during the day and night under four hot air heating modes, namely, upper air supply and lower air return, lower air supply and upper air return, two-side air supply and left air supply and right air return. The results show that the optimal air supply mode is two-side air supply.